Luminescent properties of MgAl2O4 ceramics doped with rare earth ions fabricated by spark plasma sintering technique; Ceramics International; Vol. 44, iss. 17 - Valiev D. T. Damir Talgatovich; Khasanov O. L. Oleg Leonidovich; Dvilis E. S. Edgar Sergeevich; Stepanov S. A. Sergey Aleksandrovich; Polisadova E. F. Elena Fyodorovna; Paygin V. D. Vladimir Denisovich (2018, 2018)
Title screen